Forest harvest management systems and residual phytomass affecting physical properties of a sandy soil - Sena, Karla Nascimento [UNESP]; Maltoni, Kátia Luciene [UNESP]; Troleis, Maria Júlia Betiolo [UNESP]; Faria, Glaucia Amorim [UNESP] (Revista Brasileira de Ciencia do Solo, 2021)
Organic carbon introduced in soils, mainly through organic matter, has a relevant role in various soil properties and is particularly important in sandy soils. In these soils, the input of organic material is necessary to ensure the sustainability of production systems. This study aimed to investigate the changes in total organic carbon content and its effect on physical properties in areas under different harvest management systems (HMS) after the harvest of eucalyptus. The study was performed in December 2017 in a Eucalyptus urograndis (clone E13) commercial plantation, in the municipality of Água Clara, Mato Grosso do Sul State, Brazil. The soil of this area was classified as a sandy-textured Neossolo quartzarênico, which corresponds to Quartzipsamments. Soil samples were taken from the 0.00-0.05, 0.05-0.10 and 0.10-0.20 m layers for determinations of aggregate stability, soil bulk density (BD), macroporosity (Macro), microporosity (Micro), total porosity (TP) and total organic carbon (TOC); and for calculation of carbon stock (CS). Total organic carbon and CS continued down into the 0.20-0.40, 0.40-0.60, 0.60-0.80, and 0.80-1.00 m layers. Soil mechanical penetration resistance (PR) was determined to the 0.40 m depth in 0.10 m intervals. Carbon content was evaluated in the aggregates of the 0.00-0.05 m layer after wet sieving in 2000, 1000, 250 and 53 µm diameter sieves. Statistical evaluation consisted of analysis of variance, the Tukey test, and regression for the sources of variation that showed significance at 5 %. The data suggest that keeping the residual phytomass on the soil surface can positively impact total organic carbon, with a smaller reduction under the cut-to-length harvest management system. However, carbon stock is greater at the layer of 0.20-0.60 m; as the soil has a sandy texture, carbon moves through the soil profile, which has lower soil mechanical penetration resistance at the surface layers (0.00-0.10 m), once more under the cut-to-length system. Maintaining crop residual phytomass on the soil surface in the cut-to-length harvest management system provides better soil physical conditions, with greater macroporosity (0.00-0.05 m), aggregates with more carbon, and lower soil mechanical penetration resistance compared to systems that maintain only part of the harvest residual phytomass or no residual phytomass on the surface.
Keywords: Aggregates; Carbon stock; Eucalyptus sp; Organic matter; Physical quality